The effect of moderate intensity exercise in the postprandial period on the inflammatory response to a high-fat meal: an experimental study. Issue 1 (December 2015) - Teeman, Colby; Kurti, Stephanie; Cull, Brooke; Emerson, Sam; Haub, Mark; Rosenkranz, Sara
Abstract Background Consuming a high-fat meal (HFM) may lead to postprandial lipemia (PPL) and inflammation. Postprandial exercise has been shown to effectively attenuate PPL. However, little is known about the impact of postprandial exercise on systemic inflammation and whether PPL and inflammation are associated. The purpose of this study was to determine whether moderate intensity exercise performed 60 min following a true-to-life HFM would attenuate PPL and inflammation. Methods Thirty-nine young adults (18–40 year) with no known metabolic disease were randomized to either a control group (CON) who remained sedentary during the postprandial period or an exercise (EX) group who walked at 60 % VO2peak to expend ≈ 5 kcal/kgbw one-hour following the HFM. Participants consumed a HFM of 10 kcal/kgbw and blood draws were performed immediately before, 2 h and 4 h post-HFM. Results At baseline, there were no differences between EX and CON groups for any metabolic or inflammatory markers (p  > 0.05). Postprandial triglycerides (TRG) increased from baseline to 4 h in the EX and CON groups (p  < 0.001), with no differences between groups (p  = 0.871). High density lipoprotein cholesterol (HDL-C) decreased in both groups across time (p  < 0.001) with no differences between groups (p  = 0.137). Interleukin-6 (IL-6) was significant as a quadratic function over time (p  = 0.005), decreasing from baseline to 2 h then increasing and returning to baseline at 4 h in all participants with no difference between groups (p  = 0.276). Tumor necrosis factor-alpha (TNF-α) was not different from baseline to 4 h between groups (p  > 0.05). There was an increase in soluble vascular adhesion molecule (sVCAM-1) from baseline to 4 h (p  = 0.027) for all participants along with a group x time interaction (p  = 0.020). Changes in TRG were associated with changes in interleukin-10 (IL-10) from 0 to 2 h (p  = 0.007), but were not associated with changes in any other inflammatory marker in the postprandial period (p  > 0.05). Conclusions Despite significant increases in PPL following a HFM, moderate intensity exercise in the postprandial period did not mitigate the PPL nor the inflammatory response to the HFM. These results indicate that in populations with low metabolic risk, PPL and inflammation following a HFM may not be directly related.